Interactions between the beet cyst nematode, Heterodera schachtii (Schmidt), sugar beet and Brassica trap crops - Wright, Alistair John Douglas (2018)
The beet cyst nematode (BCN), Heterodera schachtii (Schmidt), is a commonly occurring and widespread pest of sugar beet (Beta vulgaris ssp. vulgaris) which is found in all regions of the world where sugar beet is grown. The nematode feeds on the fibrous roots of suitable host plants, restricting their growth through impeded water and nutrient uptake and can reduce yield by up to 50%. BCN infestations require careful long term management to limit their spread and reduce yield losses.